Decision-making in the detection and management of patients with sepsis in resource-limited settings: the importance of clinical examination - Haniffa, R; Beane, A; Dondorp, A (BioMed Central, 2018)
We read with interest the study by Andrews et al. and the related correspondence from Shrestha et al.. We share the concern that clinical examination (and observations) appear(s) to be perceived as relatively unimportant in both the detection of the unwell patient and in the titration of interventions such as fluids, oxygen, antibiotics and vasopressors in LMICs. Studies have highlighted the limited availability of clinical observations in acutely unwell LMIC settings, which in addition to hindering detection of the deteriorating patient also complicates evaluation of an individual’s treatment and standards of care evaluation; for example, the assessment and implementation of early warning scores and prognostic models. In settings where potential for rescue by resourceintense interventions (e.g. ventilation) is remote, we too are surprised by the absence of a more central role for clinical examination and observations. It is of further concern that such limitations remain in the relatively highresource, high-visibility environment of a clinical trial.